Un conjunto epigráfico excepcional en la abadía cisterciense de Veruela (History Journal «Jerónimo Zurita», 2023)
Edition and study of the ambitious cycle of consecrational and foundational inscriptions partially conserved in the Cistercian abbey of Santa María de Veruela.
Keywords: Medieval Epigraphy; Altars; Consecration; Cistercian Order; Santa María de Veruela